Любовь online: повесть / С. Лубенец - Лубенец Светлана (Дневник первой любви, 2011)
Экземпляры: ф.13 (2012) / Инвентарный номер: 48568 / Цена: / Сис.шифр: 84(2Рос-Рус)6 / Авт.знак: Л 82 / ББК: 84(2Рос=Рус)6